2006
DOI: 10.1111/j.1525-139x.2006.00221.x
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Static Pressure Ratio Recording during Angioplasty of Arteriovenous Graft Stenosis

Abstract: Intra-access static pressure ratio (SPR) (intra-access pressure/mean arterial pressure) can be measured during angioplasty (PTA) to assess the functional importance of an arteriovenous graft (AVG) stenosis. We used SPR in 70 patients with AVGs who underwent 98 angioplasty procedures. SPR was measured during angioplasty by placing a catheter tip at mid-access. Inflow stenosis (IF) = stenosis proximal to the tip of the catheter. Outflow stenosis (OF) = stenosis distal to the tip of the catheter up to the superio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 17 publications
0
17
0
Order By: Relevance
“…These patients are prone to developing clinically significant venous hypertension due to the high rate of venous blood return. The mean blood flow in mature fistulae ranges from 780 to 1204 ml/min (25,26) and in grafts 1109 ml/min (27). In some cases, vascular access flow rates exceed 2000 ml/minute (28).…”
Section: Central Venous Stenosis Associated With Ciedsmentioning
confidence: 99%
“…These patients are prone to developing clinically significant venous hypertension due to the high rate of venous blood return. The mean blood flow in mature fistulae ranges from 780 to 1204 ml/min (25,26) and in grafts 1109 ml/min (27). In some cases, vascular access flow rates exceed 2000 ml/minute (28).…”
Section: Central Venous Stenosis Associated With Ciedsmentioning
confidence: 99%
“…Finally, angioplasty treatment of outflow stenosis causes an increase in Q combined with a decrease in VP (35). This important observation also suggests that VP measurements during angioplasty procedures may help to confirm successful treatment of hemodynamically significant stenosis.…”
Section: Discussionmentioning
confidence: 72%
“…Finally, the uses of pressure measurement to determine if a gradient was present in the setting of vascular stenosis has been a technique used within the field of Interventional radiology for a long time. It has been demonstrated that catheter directed pressure measurements and determination of a pressure gradient can determine the significance of a stenosis with relative ease and at minimal cost . This provides instantaneous diagnostic information about the stenosis in question allowing prompt treatment to occur .…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that catheter directed pressure measurements and determination of a pressure gradient can determine the significance of a stenosis with relative ease and at minimal cost. 9 This provides instantaneous diagnostic information about the stenosis in question allowing prompt treatment to occur. 9 The case presented unfortunately, the ability to perform such measurements could not occur due to technical issues with measurement equipment however it is recognised that catheter based pressure measurements is a valid alternative in procedures as previously described.…”
Section: Discussionmentioning
confidence: 99%